Characterization of planar flaws by an integrated approach using phased array and synthetic aperture focusing technique. (December 2019) - Nanekar, Paritosh; Jothilakshmi, N.; Kumar, Anish; Jayakumar, T.
Highlights: Integrated approach using PA and SAFT has been used to characterize planar flaws. The technique is found to be better than FMC + TFM for thick components. The depth of simulated and real planar flaws is assessed accurately within ±0.3 mm. Abstract: Two sound beam focusing techniques viz. phased array (PA) and synthetic aperture focusing technique (SAFT) are used during ultrasonic non-destructive testing. While PA involves sequential excitation of elements in an array using focal laws, SAFT is a post-processing algorithm involving time-shifting, summation and averaging of A-scan signals acquired by a divergent sound beam. An integrated approach using PA and SAFT has been developed in the authors' laboratory for sound beam focusing. The approach is utilized to accurately locate the extremities of planar flaws for their characterization in terms of depth and orientation. The technique is employed for characterization of simulated planar flaws in stainless steel plates and lack of sidewall fusion in a weld joint. The results obtained by PA-SAFT are found to be very accurate and comparable to the ones obtained by an advanced and a well-established array based technique called Full Matrix Capture – Total Focusing Method.